Everblaze - Messenger, Shannon (New York : Aladdin, 2014)
Sophie's talents are getting stronger and, with the elusive Black Swan group ignoring her calls for help, she is determined to find her kidnappers but a daring mistake pushes her world to the edge of war, and soon she has exposed a a major conspiracy that could threaten all she loves.
Ages 8-12.
Keywords: Ability -- Fiction; Psychic ability -- Fiction; Identity -- Fiction; Foster parents -- Fiction; Elves -- Fiction; Fantasy